Temporalities of Arrival: Burundian Barbershops as an Arrival Infrastructure in a South African Township - Nomkhosi A. Mbatha; Leah Koskimaki (Urban Planning)
Migrants from Sub-Saharan Africa have contributed to the diversity of the informal economy in urban South Africa. However, they have faced xenophobic violence and discrimination in urban spaces such as townships, which were previously designated only for Black people during apartheid. This article explores how arrival infrastructures in the township informal economy have enabled or hindered economic opportunities for those who have newly come to South Africa. Based on qualitative research on practices of solidarity and conviviality with migrant informal traders from Burundi, the Democratic Republic of Congo, and Malawi in the township of Umlazi in Durban, South Africa, in 2023, the article specifically focuses on Burundian migrants’ barber businesses as a node in the arrival infrastructure. These barbershops act as informal social spaces that provide access to “connectors” who help with networks to acquire labour, social, and material resources. These include local knowledge and information about new locations to construct a barber business or introductions to property owners. This article argues, however, that informal market and business spaces are often temporary for migrants who are always on the move, continually arriving and re-negotiating their belonging due to multiple waves and threats of xenophobic violence. Therefore, the barber business represents a temporary structure for futuring in uncertain times.